IEEE INFOCOM 2003. Twenty-Second Annual Joint Conference of the IEEE Computer and Communications Societies (IEEE Cat. No.03CH37
DOI: 10.1109/infcom.2003.1209246
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a single-wavelength optical buffer

Abstract: Abstract-We present a detailed analysis of the loss performance in an optical buffer having access to a single outgoing channel. Such a system -consisting of a number of fiber delay lines -differs significantly from a conventional electronic buffer, in that only a discrete set of delays can be realized for contention resolution.This leads to an underutilization of the channel capacity, which reduces overall performance.Our analysis does not require any special assumptions about the burst-or packet-size distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
1

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(82 citation statements)
references
References 8 publications
(4 reference statements)
3
78
1
Order By: Relevance
“…Under the assumptions of Poisson arrivals and independent packet length distribution, in [5], [10], [11] the duration of void period is considered to be uniformly distributed over the interval with mean . Recall that the optical buffer shown in Fig.…”
Section: A Busy Period With Exceptional Service For the First Packetmentioning
confidence: 99%
See 2 more Smart Citations
“…Under the assumptions of Poisson arrivals and independent packet length distribution, in [5], [10], [11] the duration of void period is considered to be uniformly distributed over the interval with mean . Recall that the optical buffer shown in Fig.…”
Section: A Busy Period With Exceptional Service For the First Packetmentioning
confidence: 99%
“…This problem is equivalent to the analytical analysis of an queue with bounded waiting time , where the can be infinite and which makes it infeasible to get a steady state equation like (6) and thus an analytical result on its distribution. That is why the widely adopted approach now is to get the distribution of the above finite queue through analyzing its corresponding infinite queue counterpart without waiting time limit [17]- [20], which results in the offered load constraint of (11) for the stability guarantee of the infinite queue.…”
Section: B Packet Blocking Probabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike conventional electronic buffers, however, it cannot delay bursts for an arbitrary period of time, but it can only realize a discrete set of N delay values. In [9,2] it is shown that this leads to voids on the outgoing channel. We do not attempt to fill these voids (as this would alter the order of the bursts).…”
Section: Fibre Delay Linesmentioning
confidence: 99%
“…Several architectures that make use of an FDL buffer have already been identified [3], [4], [8]. The main performance measure of an FDL buffer is its loss rate and analytic and simulation based results concerning the loss rates have been reported in [2], [5], [6], [9], [10], [12].…”
Section: Introductionmentioning
confidence: 99%